Sistem Informasi Reservasi Wisata Camping Menggunakan Mapping (Studi Kasus : Bumi Perkemahan Dlundung Mojokerto) - Fuad Azis Muslim; Hamzah Setiawan; Nuril Lutvi Azizah; Ade Eviyanti (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The Dlundung campground is one of the campsite attractions located in Ketapanrame village, sub-district. Trawas, Mojokerto Regency, East Java. Dlundung campground provides campsites divided into blocks. There are 5 camping blocks in this camping area. At Dlundung Campground, of course, there is a business process that is implemented to manage and regulate all activities carried out, especially business processes to manage the reservation process and process payments made by tourists. because the promotional media is still minimal, the reservation records that often the managers at the Dlundung campground provide incorrect information regarding reservations. In addition, the Dlundung campground also experienced difficulties in managing its payment system. Because there is no guarantee at the outset such as a DP (down payment), tourists who have made reservations often do not come without giving prior notification to the detriment of the Dlundung Campground. Based on the problems that occurred at the Dlundung Mojokerto Camping Ground along with the results of interviews with Dlundung Mojokerto Camping Ground staff, a reservation information system is needed to manage the reservation process and also payment. This system will be developed on a web basis because it is easier to use and later this system will be integrated with the Midtrans Application Programming Interface (API) so that it can bridge the payment process between tourists and the Dlundung Mojokerto Camping Ground.